376 الذكاء الاصطناعي وتطبيقاته في دعم أدوار مراكز الفكر: دراسة استشرافية : Artificial Intelligence and Its Applications in Enhancing the Think Tank Roles: A Foresight Study - بسمة الحداد ماجدة إبراهيم ، هبة جمال الدين وأخرون (معهد التخطيط القومي, 2026)
تهدف الدراسة إلى تحليل دور الذكاء الاصطناعي في تطوير أداء مراكز الفكر وتعزيز قدرتها على دعم صنع السياسات العامة. اعتمدت على منهجية متنوعة جمعت بين التحليل الوصفي ودراسة التجارب الدولية والأدوات الاستشرافية. وأظهرت النتائج أن الذكاء الاصطناعي يسهم في تحليل البيانات واستشراف المستقبل ودعم السياسات القائمة على الأدلة. كما كشفت عن وجود تحديات تتعلق بالبنية التحتية والتمويل والمهارات البشرية والحوكمة الأخلاقية. وقدمت الدراسة نموذجًا وطنيًا لتوطين الذكاء الاصطناعي في مراكز الفكر بما يدعم التنمية المستدامة وصنع القرار. The study explores the role of artificial intelligence in strengthening think tanks’ functions and sustainability amid rapid technological change. It proposes a framework for integrating AI into research, policy analysis, advisory work, and engagement while preserving independence. A mixed-methods approach is used, including case studies, foresight tools, and comparative analysis of AI strategies. Findings show a gap between AI’s potential in decision support and its actual adoption due to infrastructure, funding, and skills challenges. The study presents a roadmap for AI-enabled think tanks to improve policymaking and development planning in a responsible way.